Some ecological aspect of mustard aphid Lipaphis erysimi, infestation on broccoli (Brassica oleracea) and efficacy of bio-insecticides for management of mustard aphid in Bangladesh - Parven, N; Azad, R B; Kumar, A; Shanti, S J; Sultan, M Z; Akimoto, S I; Begum, S (Journal of Biodiversity Conservation and Bioresource Management, 2025)
Brassica oleracea (broccoli) is a major, economically important, and commercially produced winter vegetable in Bangladesh. A study was conducted on the ecology of the mustard aphid, Lipaphis erysimi and the bio-efficacy of bio-insecticides (Biotrin and Ecomac) against L. erysimi using leaf dipping methods at different doses. L. erysimi was recorded as a destructive and major pest of broccoli. This aphid species infested broccoli as a secondary host plant, invading the leaves and shoots during the early harvesting season (December to January). The infestation continued and infested the entire vegetative parts during the peak and late cropping seasons. Aphid incidence was significantly higher (1171.62 ± 11.14) in April but declined drastically (42.25 ± 3.2) from May when seasonal temperature increased. The results demonstrated that compared with the control (untreated) aphids, the Biotrin and Ecomac treated doses induced significant mortality (F = 3.76, df = 2, P < 0.05) of the aphids. Greater concentrations (1.4 ml/1000) of both bio-insecticides significantly reduced fitness traits (reproduction and survival rate) of L. erysimi's (F = 18.57, df = 2, P < 0.001). The mixed bio-insecticides (Biotrin 1: Ecomac 1) were most effective for 24 h. It caused the highest rate of mortality (81.31 ± 14.75) followed by Ecomac (65.62±25.83) and Biotrin (52.71±15.07). However, the mortality rate of aphids was declined at 73.85±15.84 after 48 h, indicating that the synergistic effects of mixed insecticides gradually decreased. After 48 h of treatment, the mortality rate of Ecomac and Biotrin treated aphids was significantly higher (F = 22.74, df = 2, P < 0.001). This study will provide important information on seasonal infestation intensity, interactions with L. erysimi and bio-efficacy of bio-insecticides. The use of bio-insecticides may be an effective control measure for aphid management in Bangladesh. J. biodivers. conserv. bioresour. manag. 10(2), 2024: 107-120